Living and Learning in the Shadow of the Shopocalypse: Reverend Billy’s Anti-consumption Pedagogy-of-the-Unknown as Critical Adult Education - Jennifer Sandlin (Adult Education Research Conference, 2007)
I explore the social movement learning operating within one site of critical public pedagogy and, specifically, examine how the anti-consumption activist group Reverend Billy and the Church of Stop Shopping fosters participatory cultural production, enacts a poetic community politics, and encourages transitional spaces of learning through a pedagogy-of-the-unknown.